2018
DOI: 10.1093/annonc/mdx730
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CD73 in triple-negative breast cancer: multiplex analysis of a phase III clinical trial

Abstract: Taken together, our study provides further support that CD73 expression is associated with a poor prognosis and reduced anti-tumor immunity in human TNBC and that targeting CD73 could be a promising strategy to reprogram the tumor microenvironment in this BC subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(144 citation statements)
references
References 25 publications
(30 reference statements)
8
135
0
1
Order By: Relevance
“…Hence, the development of targeted CD73/A2aR adenosine signaling therapies requires the effective stratification of patients to recognize the therapeutic potential of these approaches. In triple‐negative breast cancer, CD73 expression on epithelial tumor cells had a significant negative correlation with CD45 + immune cell infiltration, and patients with high CD73 epithelial expression as well as low CD45 + immune cell infiltration had the worst survival . In our study, we found that DLBCL patients with CD73 positivity on tumor cells as well as low CD8 + immune cell infiltration had the worst survival, and DLBCL patients with CD73 negativity on tumor cells as well as high CD8 + immune cell infiltration had the best clinical outcome.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Hence, the development of targeted CD73/A2aR adenosine signaling therapies requires the effective stratification of patients to recognize the therapeutic potential of these approaches. In triple‐negative breast cancer, CD73 expression on epithelial tumor cells had a significant negative correlation with CD45 + immune cell infiltration, and patients with high CD73 epithelial expression as well as low CD45 + immune cell infiltration had the worst survival . In our study, we found that DLBCL patients with CD73 positivity on tumor cells as well as low CD8 + immune cell infiltration had the worst survival, and DLBCL patients with CD73 negativity on tumor cells as well as high CD8 + immune cell infiltration had the best clinical outcome.…”
Section: Discussionsupporting
confidence: 46%
“…In triplenegative breast cancer, CD73 expression on epithelial tumor cells had a significant negative correlation with CD45 + immune cell infiltration, and patients with high CD73 epithelial expression as well as low CD45 + immune cell infiltration had the worst survival. 25 In our study, we found that DLBCL patients with CD73 positivity on tumor cells as well as low CD8 + immune cell infiltration had the worst survival, and DLBCL patients with CD73 negativity on tumor cells as well as high CD8 + immune cell infiltration had the best clinical outcome. A similar phenomenon was also observed using the ALCs in the peripheral blood instead of CD8 + immune cell infiltration in tissue.…”
Section: Discussionsupporting
confidence: 46%
“…These mice also benefit from increased chemotherapy sensitivity (36,71) and reduced angiogenesis (71,72). In line with these studies, many human tumors overexpress CD73 and associates with poor prognosis (36,(73)(74)(75)(76)(77)(78). CD73 is also linked to drug resistance, epithelial-to-mesenchymal transition (EMT), and cancer cell proliferation and stemness (76,(79)(80)(81)(82)(83)(84).…”
Section: Cd73 and Adenosine Receptor Activity Promotes Immunosuppressionmentioning
confidence: 78%
“…This has now been confirmed in human patients as data from the BIG-02-98 study conclude that high levels of CD73 expression on epithelial tumor cells positively associates with reduced DMFS and OS and negatively correlates with tumor immune cell infiltration (Spearman's r = -0.50, P < 0.0001). Patients with high levels of CD73 and low levels of tumorinfiltrating leukocytes had the worse clinical outcome [34] . This suggests that adenosine signaling in TNBC associates with poor patient survival and that targeting CD73 or A2BR may provide a Overall survival (OS) and distant metastasis free survival (DMSF) were compared and median survival calculated using km plotter.…”
Section: Adenosine Receptor 2b Functioning In Tnbcmentioning
confidence: 99%